Faktor resiko terjadi infestasi kutu pada anak-anak di panti asuhan - Haritharan Ganesan; Putu Ayu Asri Damayanti (DiscoverSys Inc., 2017)
Infestation with lice is most common among preschool- and elementary school-age children and their household members and caretakers hence becoming an increasing problem in orphanage because of the poor hygiene and knowledge of children on lice. This study explores about the risk factor of knowledge, social risk and personal risk among the students who are living in the orphanage. Study design chosen for this research is descriptive study with 98 student from two orphanages home as respondents. Questionnaires were given to answer to all the 98 respondents. The questionnaire were subdivided into three section to determine the respondent’s knowledge, social and personal risk. Later on the risk factors were evaluated according to the score and categorized into categories to determine the risk level. Among all the 98 respondents it is known most of the students have adequate knowledge about lice and infestation of lice shows that the students knows about lice, and average risk in social history which shows there is a chance of infestation from this risk factor because of the close living conditions, it was also show that the students have good personal history which shows that the responders have good personal behavior and hygiene, the risk factors was also researched using the difference between the orphanages and the age of the responder for a better understand of the risk factor. Thus, it is concluded that lice infestation risk in the orphanage is low considered as the students have adequate knowledge, social and personal risk. The results of this research could be applied as an analytical studies for further research in lice infestation.